PENGGUNAAN MEDIA PEMBELAJARAN KONKRIT UNTUK MENINGKATKAN AKTIFITAS BELAJAR DAN PEMAHAMAN KONSEP PECAHAN MATA PELAJARAN MATEMATIKA SISWA KELAS III MI MA’ARIF NU SUKODADI-LAMONGAN - Retno Nuzilatus Shoimah; Mustika Syafi'aturrosyidah (MIDA : Jurnal Pendidikan Dasar Islam, 2021)
Abstract This study aims to investigate the effect of the use of concrete learning media on mathematics subjects in fractional material at MI Ma'arif NU Sukodadi-Lamongan. Concrete media is used to make it easier for students understanding of the concept of fractions and fractional operations. The research method used is qualitative research in descriptive qualitative. The results of the study showed a significantly increase in learning activities and understanding the fractions concepts and fraction operations. Before using concrete learning media, the results of the assessment of student learning activities were obtained as follows: 3 students were very active (12%), 7 students were active (29%), 10 students were quite active (42%), and 4 students were inactive (17%). Whereas after using concrete media the following results were obtained: 13 students were very active (54%), 7 students were active (29%), 4 students were quite active (17%), and 0 students were inactive (0%). The results of the assessment of the understanding of the concept of fractions on students were obtained through written tests in the form of giving a description item with many 5-item questions. Before using concrete learning media, the following assessment results were obtained: 18 students did not pass the KKM (75%), 6 students passed the KKM (25%), and the average student score was 71 (did not reach the KKM). Whereas after the use of concrete media the following results were obtained: 1 student did not pass the KKM (7%), 23 students passed the KKM (93%), and an average student score of 91 (reached KKM). Keyword: mathematics, fractions, concrete learning media Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media pembelajaran konkrit pada mata pelajaran matematika materi pecahan di MI Ma’arif NU Sukodadi-Lamongan. Media konkrit digunakan untuk mempermudah siswa memperoleh pemahaman konsep pecahan dan operasi bilangan pecahan sederhana dengan tepat dan cepat. Metode penelitian yang digunakan adalah penelitian kualitatif dengan bentuk descriptive kualitatif. Hasil penelitian menunjukkan adanya peningkatan yang cukup signifikan pada aktifitas belajar dan pemahaman konsep pecahan dan operasi pecahan. Sebelum penggunaan media pembelajaran konkrit, diperoleh hasil penilaian aktifitas belajar siswa sebagai berikut: 3 siswa sangat aktif (12%), 7 siswa aktif (29%), 10 siswa cukup aktif (42%), dan 4 siswa tidak aktif (17%). Sedangkan setelah penggunaan media konkrit diperoleh hasil sebagai berikut: 13 siswa sangat aktif (54%), 7 siswa aktif (29%), 4 siswa cukup aktif (17%), dan 0 siswa tidak aktif (0%). Hasil penilaian pemahaman konsep pecahan pada siswa diperoleh melalui tes tulis berupa pemberian soal uraian dengan banyak soal 5 butir. Sebelum penggunaan media pembelajaran konkrit, diperoleh hasil penilaian sebagai berikut: 18 siswa tidak lulus KKM (75%), 6 siswa lulus KKM (25%), dan rata-rata nilai siswa 71 (tidak mencapai KKM). Sedangkan setelah penggunaan media konkrit diperoleh hasil sebagai berikut: 1 siswa tidak lulus KKM (7%), 23 siswa lulus KKM (93%), dan rata-rata nilai siswa 91 (mencapai KKM). Kata kunci: matematika, pecahan, media konkrit